Varietal Characterization of Rice (Oryza sativa L.) based on Morphological Descriptors - MONIKA A. JOSHI,; NAVRAJ K. SARAO,; R.C. SHARMA,; PRITHPAL SINGH,; T.S. BHARAJ, (Seed Research, 2026)
Nineteen varieties of rice (Oryza sativa L.) belonging to non-basmati and basmati group were characterized based on fifty-two morphological descriptors at different stages of plant growth. The present experimental material possessed considerable variability and heritability coupled with moderate to high genetic advance for most of the morphological traits, thus signifying their utility in the varietal characterization. Although the cultivars showed overlapping of descriptor expression in various combination traits, still the identity of all the cultivars in non-basmati as well as basmati group could be established individually and could thus, be helpful for the registration/protection of these varieties.